The Effect of Cognitive Behavioral Group Therapy on Children’s Self-Esteem - Naomi Epel (MDPI AG, 2021)
(1) Background: Self-esteem plays an important role in developing emotional resilience and wellbeing in children. Yet, there has been little related research on Cognitive Behavioral Group Therapy on this topic. Our aims were to assess the effect of the Child Self-Esteem CBT (CSE-CBT) protocol on children’s self-esteem in grades five and six; to assess the effect of the CSE-CBT protocol on the therapeutic process; and to explore the feasibility of delivering the CSE-CBT protocol in a school setting. (2) Methods: Eighty elementary school children in grades five and six, divided into four intervention and four control groups, attended 12 structured sessions using the CSE-CBT protocol, led by specially trained teachers. The children completed questionnaires to assess their self-esteem at the beginning and at the end of the study, and answered weekly questionnaires that assessed therapeutic process. Hierarchical linear modeling was used to analyze the data. (3) Results: The CSE-CBT protocol had a significant effect on improving children’s self-esteem over the course of the study, regardless of the children’s working alliance with the teacher leading the group. (4) Conclusions: The findings suggest that the CSE-CBT protocol has the potential to benefit children’s self-esteem and indicate that school teachers can be trained to administer the CBT-protocol.